An Update on Targeted Treatment of IgA Nephropathy: An Autoimmune Perspective - Huang, Xin; Xu, Gaosi (Frontiers in Pharmacology, 2021)
IgA nephropathy (IgAN) is the most common form of primary glomerulonephritis worldwide, considered a significant cause of the end-stage renal disease in young adults. The exact pathogenesis of IgAN is not yet well defined. The clinical and pathological features vary a lot among individuals and races, which may increase the difficulty in IgAN treatment. Currently, existing general therapeutic strategies are not enough to improve progressive decline in renal function in most cases. With an evolving understanding of the autoimmune pathogenesis of IgAN involving a role for the immune response, mucosal immunity, renal inflammation, complement activation, and autophagy, various pharmacological therapeutic targets have emerged, and treatments based on these targets have been explored in preclinical and clinical studies. This review summarizes the emerging progress in research concerning targeted therapeutic strategies and relevant autoimmune pathogenesis in IgAN. Given the slowly progressive nature and complicated pathogenesis of IgAN, combined therapy, targeting pathogenic pathways, may provide a more rational therapeutic option soon.